2020
DOI: 10.3390/joitmc6010019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of System Management on Value Creation and Global Growth in Born Startups: Focusing on Born Startups in Korea

Abstract: This study is intended to determine the effects of system management on value creation and global growth in born startups. To achieve this, a survey was empirically carried out on 300 owners in born startups with less than five years’ experience. The findings are as follows. First, entrepreneurship, operation system, and support system as sub-variables of system management have a positive effect on value creation. Second, entrepreneurship and operating system have no significant effect on global growth, but th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The aim of this analytical step is to statistically confirm that the indicators and latent factors chosen in the previous step are robust so that the further steps are based on solid ground. This step is customary in SEM analysis [70,71].…”
Section: Confirmatory Factor Analysismentioning
confidence: 99%
“…The aim of this analytical step is to statistically confirm that the indicators and latent factors chosen in the previous step are robust so that the further steps are based on solid ground. This step is customary in SEM analysis [70,71].…”
Section: Confirmatory Factor Analysismentioning
confidence: 99%
“…The endorsement of entrepreneurship has become dramatically an essential part of the growth in both underdeveloped and developing countries [1]. The education sector has suggested that entrepreneurship is a significant contributor in generating business opportunities to minimize the dependence on employment.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, system management is a highly efficient, autonomous management system that improves competitiveness by enhancing and then maintaining continuity to link the planning, execution, and evaluation phases systematically while also systematiz-ing each step. It is thus an efficient management system that improves productivity by systematically standardizing and systematizing business processes [17]. There are several studies on management systems as key determinants of innovation performance [18][19][20].…”
Section: System Managementmentioning
confidence: 99%